Implications of heat-induced changes in bone on the interpretation of funerary behaviour and practice - Gonçalves, David (2011)
Bones submitted to heat experience structural and chromatic modifications. In particular, heat-induced bone warping and thumbnail fractures have been linked to the burning of fleshed and green bones where the soft tissues have been removed from the bones soon after death e in contrast to dry bones. Those have been suggested as indicators of the state of the individual before being burned thus allowing inferences about the funerary behaviour of archaeological populations. A large sample of 61 skeletons submitted to cremation has been examined for the presence of both of these heat-induced features. Although uncommon, bone warping and thumbnail fractures were present in some of the skeletons demonstrating that its presence is not restricted to the burning of non-dried bones as generally believed. Rather than being an indicator of the presence of bones with soft tissues, bone warping seems to be more of an indicator of the preservation of collageneapatite links which can be maintained on dry bones with low collagen deterioration. In addition, our results also do not confirm thumbnail fractures as an exclusive sign of the burning of bones with soft tissues. As a result, these heat-induced changes should be used with caution when trying to infer about the pre-burning state of an individual.